Safety evaluation of fermented fish and shellfish products I. microbiological contaminants - Mabesa, R.C; Castillo, M.M; Revilla, S.V; Bandian, V.T (1983)
Total plate counts and specific tests for indicator organisms were performed on fermented fish and shellfish samples collected from different regions of the Philippines from December, 1980 to December 1981. Microorganisms of public health significance detected and enumerated were the fecal coliforms, staphylococci, salmonellae and vibrios. Results revealed that coliforms predominatedin many of the samples analyzed, staphylococci occurred moderately while salmonellae and vibrios were only ocassionally detected. Samples from the Bicol and Visayas regions were grossly contaminated while those from Northern Luzon were less contaminated.